Pengaruh Perilaku Hedonisme, Shopping Lifestyle Dan Fasilitas Terhadap Perilaku Konsumtif Pengguna Tiktokshop Di Kalianda Lampung Selatan - Syarif, Hyliyas; Tamam, Tamam (CV. ITTC INDONESIA, 2024)
In the current digital era, consumer behavior is increasingly influenced by the development of e-commerce platforms and social media, including TikTok Shop which has developed rapidly as an online shopping platform, which combines entertainment with ease of shopping. This has led to an increase in consumer behavior among users, especially those triggered by hedonistic behavior, shopping lifestyle and facilities provided by the platform. This behavior needs to be studied further considering its impact on people's consumption patterns. This study aims to determine the effect of Hedonistic Behavior, Shopping Lifestyle, and Facilities on the Consumer Behavior of TikTok Shop Users in Kalianda, South Lampung. The research method used is a type of Causal study with a quantitative approach, in this case the population and sample used are the community in Kalianda, South Lampung as many as 97 respondents. The research instrument uses a questionnaire and documentation with data sources from primary and secondary data, in analyzing using multiple linear regression test analysis. The results of the study indicate that hedonistic behavior has a positive and significant effect on consumer behavior of Tiktokshop users with a t-count value of 2.421> t-table 1.661 and a significance level of 0.000 <0.05, then shopping lifestyle also has a positive effect. While facilities do not affect consumer behavior of Tiktokshop users in Kalianda, South Lampung. The t-count value is 1.369 <t-table 1.661 and a significance level of 0.174> 0.05. The results of the simultaneous F test show that all independent variables together have a significant effect on consumer behavior of Tiktokshop users. The results of this study are expected to contribute to similar variables in further research..